Postharvest Quality and Shelf-Life Performance of Nineteen Carrot Genotypes - Nafisa Anjum; Md Harun Ar Rashid; Md Golam Rabbani; Mst Fatema Tuz Zahura (Research in Agriculture Livestock and Fisheries, 2025)
Carrots (Daucus carota L.) belong to the family Apiaceae, are one of the world's most important root crops. The experiment was conducted at the Postharvest Laboratory of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period from February-March 2024 to study performance of postharvest quality and shelf life of the nineteen carrot genotypes namely Kuroda, New Kuroda, Kuroda 35, King Kuroda, Shin Kuroda, Kuroda Improved, Shidur, Pusha Keshor, Bankim Keshor, Orange HYV, Brasilia 2007, BAU Gazor 5, Brasilia Agroflora, Prima Agroflora, Gazor lovely, Autumn King 2, Nantes 5, 16ˊB114-1 and 21408B. Results revealed that carrot genotypes significantly influenced all the parameters under study. The maximum dry matter content (13.39%) and TSS content (23.27% brix) were obtained from Pusha Keshor and 21408B, respectively. The minimum weight loss (14.19%) was observed in Gazor lovely while the maximum weight loss (42.25%) was recorded in 21408B. The highest disease incidence (66.67%) was recorded in Orange HYV, whereas the maximum disease severity (66.52%) was observed in 21408B, and no disease incidence was recorded in Kuroda 35. The longest shelf life (12.14 days) was observed in Kuroda 35 while the shortest (7.08 days) was observed in Orange HYV. Therefore, it can be concluded that Kuroda 35 was found to be better in respect of postharvest quality and shelf life compared to the other carrot genotypes. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 121-135